Genetic characterization of Rosa species using morphological markers - GAURAV, ABHAY KUMAR; NAMITA, NAMITA; RAJU, D V S; SINGH, MARKANDEY; SINGH, BHUPINDER; KRISHNAN, S GOPALA; MITHRA, S V AMITHA; PANWAR, SAPNA; SINGH, MOHAR; DHIMAN, M R (The Indian Journal of Agricultural Sciences, 2018)
Genetic diversity in roses is unparalleled to any other flower crops. A large number of rose species is grown all around the world. There is a rich wealth of indigenous rose species such as Rosa brunonii, R. macrophylla, R. moschata, R. spinossisima, R. rubiginosa, R. wichuraiana etc. are grown wild in India. They are the important source of genes responsible for various traits, viz. both biotic and abiotic stress tolerance, fragrance, perpetual flowering, hardiness which need to be protected for further use in breeding programs. Morphological markers or traits based species identification are best for visualization, reproducibility and easy to use, besides serving as a reality check for molecular studies. In this study, 31 rose species were characterized for 18 vegetative characters as per PPV FRA guidelines for DUS testing of rose. Genetic diversity of rose species was done based on dissimilarity calculation, hierarchical cluster analysis, linear discriminant analysis and principal component analysis using R software. R. banksiae - R. chinensis‘Viridiflora’ and R. banksiae - R. rubiginosa showed the highest diversity while R. brunonii and R. dumalis shows least diversity. Species were divided into five major clusters using hierarchical cluster analysis which was validated by linear discriminant analysis. Here, both Indian originating species R. brunonii and R. moschata fell into the same cluster while significant diversity noticed in R. damascena and R. wichuraiana. Results of principal component analysis follow a similar pattern as of dendrogram. R. banksiae was most distinctly placed which is well supported as only thornless species used in the study. Although no single morphological traits can be used to differentiate species, it is necessary to create a passport data for further studies.